Wooden Panel Deterioration by Tropical Marine Wood Borers - Singh, H.R.; Sasekumar, A. (Elsevier, 1996)
Wood destruction in test panels ofShorea leprosulawas related to the percentage of fouling, types of wood borers and the number of wood borers. The natural durability ofShorea leprosulapanels was estimated to be 4–5 months in Malaysian marine waters. A higher fouling cover resulted in lower rates of wooden panel deterioration. Larger numbers of wood borers brought about greater panel deterioration. Primary wood destruction was caused by bivalve wood borers, mainlyMartesia striata, Lyrodus pedicellatus, Bankia campanellata, Teredo furciferaandTeredo bartschi. Martesia striatawas the important wood destroying agent in the intertidal zone and, together with the shipworms, was also responsible for panel destruction in the subtidal zone.